Chrystianizacja Prus według Kroniki Jana Długosza - Bielak, Włodzimierz (Archiwa, Biblioteki i Muzea Kościelne, 2010)
Since the beginning of its existence, the Polish Church took an active part in the Christianization of the neighbouring pagan peoples. One of its missionary areas was the land inhabited by the Prussians. These missions were conducted in three stages. The first one was the mission undertaken by Saint Wenceslaus under the patronage of duke Boleslaw the Valiant (Polish: Bolesław Chrobry). During this mission St Wenceslaus died a martyr’s death, which was used as a factor promoting the Polish Church while creating metropolitan church organization in 1000. The second stage was the missionary activity at the time of Henryk Kietlicz, the archbishop of Gniezno, at the turn of the 12th and 13th centuries, which was interrupted by the appearance of the Teutonic Order in Prussia. The action of the Teutonic Knights in Prussia was the third stage of Christianization. However, this evangelization was the German method of conducting a mission- that is to say, by the sword. The objective of the Teutonic Knights was to create their own state in Prussia rather than convert pagans to Christianity. The description of these processes was based on the Annals of Jan Dlugosz, which shows how the memories of those events were retained.